Comparative evaluation of treatment with low-dose aspirin plus dipyridamole versus aspirin only in patients with acute ischaemic stroke - Arnarsdottir Lola; Hjalmarsson Clara; Bokemark Lena; Andersson Björn (BMC Neurology, 2012)
Abstract Background Previous studies have suggested that pre-stroke treatment with low-dose aspirin (A) could reduce the severity of acute ischaemic stroke, but less is known on the effect of pre-stroke treatment with a combination of aspirin and dipyridamole (A + D) and post-stroke effects of these drugs. The aim of the present study was to evaluate the effect of this drug combination on acute and long-term prognosis of ischaemic stroke. Methods Patients without atrial fibrillation admitted to the stroke unit with acute ischaemic stroke (n = 554) or TIA (n = 108) were studied during acute hospital care and up to 12 months after discharge from hospital. Results Prior to acute stroke 62 patients were treated with A + D while 247 patients were treated with A only. No beneficial effects of the combination A + D compared to A only were noted on stroke severity and/or acute in-hospital mortality. However, survival analysis by Cox-proportional hazard model demonstrated lower 12-months all-cause mortality in patients discharged with A + D (n = 275) compared with patients on A only (HR, 0.52; CI, 0.32-0.86; p = 0.011; n = 262) after adjusting for age, baseline NIHSS, previous stroke, previous myocardial infarction and type 2 diabetes. We also noted a tendency towards lower all-cause mortality at 3 months with use of A + D, but this was not statistically significant (p = 0.12). Conclusions Pre-stroke treatment with a combination of low-dose A + D does not reduce the severity of acute stroke, nor does it reduce the acute in-hospital mortality. However, treatment with A + D at discharge from hospital is seemingly associated with lower long-term mortality compared with A only, contrary to the results from previous randomised studies. However, our results must be interpreted with extreme caution considering the non-randomised study design.